Low Aflatoxin Levels in Aspergillus flavus-Resistant Maize Are Correlated With Increased Corn Earworm Damage and Enhanced Seed Fumonisin - Chalivendra, Subbaiah; Huang, Fangneng; Busman, Mark; Williams, W. Paul; Ham, Jong Hyun (Frontiers in Plant Science, 2020)
Preharvest mycotoxin contamination of field-grown crops is influenced not only by the host genotype, but also by inoculum load, insect pressure and their confounding interactions with seasonal weather. In two different field trials, we observed a preference in the natural infestation of corn earworm (CEW; Helicoverpa zea Boddie) to specific maize (Zea mays L.) genotypes and investigated this observation. The field trials involved four maize lines with contrasting levels of resistance to Aspergillus flavus. The resistant lines had 7 to 14-fold greater infested ears than the susceptible lines. Seed aflatoxin B1 (AF) levels, in mock- and A. flavus-inoculated ears were consistent with genotype resistance to A. flavus, in that the resistant lines showed low levels of AF (<30 ppb), whereas the susceptible lines had up to 500 ppb. On the other hand, CEW infestation showed a positive correlation with seed fumonisins (FUM) contamination by native Fusarium verticillioides strains. We inferred that the inverse trend in the correlation of AF and FUM with H. zea infestation may be due to a differential sensitivity of CEW to the two mycotoxins. This hypothesis was tested by toxin-feeding studies. H. zea larvae showed decreasing mass with increasing AF in the diet and incurred >30% lethality at 250 ppb. In contrast, CEW was tolerant to fumonisin with no significant loss in larval mass even at 100 ppm, implicating the low seed aflatoxin content as a predominant factor for the prevalence of CEW infestation and the associated fumonisin contamination in A. flavus resistant maize lines. Further, delayed flowering of the two resistant maize lines might have contributed to the pervasive H. zea damage of these lines by providing young silk for egg-laying. These results highlight the need for integrated strategies targeting mycotoxigenic fungi as well as their insect vectors for enhanced food safety.